2009
DOI: 10.1093/bja/aen360
|View full text |Cite
|
Sign up to set email alerts
|

Major complications of central neuraxial block: report on the Third National Audit Project of the Royal College of Anaesthetists

Abstract: The data are reassuring and suggest that CNB has a low incidence of major complications, many of which resolve within 6 months.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
465
2
26

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 809 publications
(500 citation statements)
references
References 29 publications
7
465
2
26
Order By: Relevance
“…8,9,14 The use of bedside spinal ultrasound may take us one step closer to the safer practice of neuraxial anesthesia by helping to avoid direct trauma to the spinal cord, a rare but preventable complication. 2 It is important to highlight, however, that it is not possible to visualize the conus medullaris with the current technology; therefore, there is still the possibility of trauma in cases of low lying spinal cords.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…8,9,14 The use of bedside spinal ultrasound may take us one step closer to the safer practice of neuraxial anesthesia by helping to avoid direct trauma to the spinal cord, a rare but preventable complication. 2 It is important to highlight, however, that it is not possible to visualize the conus medullaris with the current technology; therefore, there is still the possibility of trauma in cases of low lying spinal cords.…”
Section: Discussionmentioning
confidence: 99%
“…More importantly, spinal anesthesia should be performed below the level of the conus medullaris to minimize the risk of spinal cord trauma. 1,2 The clinical identification of the interspace level, which typically relies on the palpation of the iliac crests to determine the landmark, is largely inaccurate. Broadbent et al 3 demonstrated that anesthesiologists could identify a particular lumbar interspace correctly by palpation in only 29% of cases; they were one, two, three, or four spaces higher than the correct space (assessed by magnetic resonance imaging) in 51%, 15%, 2%, and 1% of cases, respectively.…”
Section: Résumémentioning
confidence: 99%
See 1 more Smart Citation
“…4 This risk is increased further in the context of an anticoagulated patient. In order to 84 reduce the risk of haematoma development, current UK and international consensus 85 guidelines recommend that performance of a neuraxial block or removal of an epidural 86 catheter should not be carried out until 10-12 h after a thromboprophylactic dose of 87 LMWH.…”
mentioning
confidence: 99%
“…Data from the Royal College of Anaesthetists National Audit Project 3 revealed that from approximately 700,000 central neuraxial blocks performed annually in the NHS, 40% are epidurals. Incidence of permanent harm from all epidurals ranged from 3.1 in 100,000 to 6.1 in 100,000 [2]. Harm in these circumstances denotes vertebral abscess, haematoma and direct nerve injury.…”
Section: Introductionmentioning
confidence: 99%